Hubungan Kesejahteraan Spiritual dengan Kualitas Hidup Pasien Hemodialisis - Khoirunnisak Khoirunnisak; Indah Sri Wahyuningsih; Mohammad Arifin Noor (Jurnal Ventilator, 2025)
Chronic kidney failure is a terminal illness that requires hemodialysis therapy to sustain life. However, this therapy often impacts patients' quality of life, including physical, mental, social, and spiritual aspects. Low spiritual well-being can significantly affect the quality of life, causing stress, anxiety, and a decline in emotional balance. This research aims to analyze the relationship between spiritual well-being and the quality of life of hemodialysis patients, providing insights to support the improvement of their quality of life. This study is a type of Quantitative research with an Observational Analytic research design with a correlational study. Data collection was carried out using the KDQOL-SF and SWBS questionnaires. The number of respondents was 61 people with a total sampling technique. The obtained data were statistically processed using the Chi-square test. The result of this study shows that there is a relationship between spiritual well-being and the quality of life of hemodialysis patients with a P value = 0.000 (P value < 0.05). This study concludes that there is a significant relationship between spiritual well-being and the quality of life of hemodialysis patients. Improving spiritual well-being can enhance patients' quality of life; therefore, it is important to provide spiritual support in therapy to help patients overcome their health challenges.